$5^{2n}=(5^2)^n=25^n$ De la misma manera, $2^{5n}=32^n$
$$\text{So, }5^{2n}-2^{5n}=25^n-32^n$$
Ahora,
(1) $(a^n-b^n)(a+b)=a^{n+1}-b^{n+1}+ab(a^{n-1}-b^{n-1})$
$\implies a^{n+1}-b^{n+1}=(a^n-b^n)(a+b)-ab(a^{n-1}-b^{n-1})$
Si $(a-b)$ divide $(a^{n-1}-b^{n-1}),(a^n-b^n)$
se dividirá $ (a^{n+1}-b^{n+1})$
Ahora, $(a-b)\mid (a-b)$ y $(a-b)\mid (a^2-b^2)$
(2) $(a-b)(a^n+b^n)=a^{n+1}-b^{n+1}-ab(a^{n-1}-b^{n-1})$
$\implies a^{n+1}-b^{n+1}=(a-b)(a^n+b^n)+ab(a^{n-1}-b^{n-1})$
Así que, $(a-b)\mid (a^{n+1}-b^{n+1})\iff $ divide $(a^{n-1}-b^{n-1})$
Ahora, $(a-b)\mid (a-b)$ y $(a-b)\mid (a^2-b^2)$
Aquí $a=25,b=32$